CHANGES IN THE QUALITY OF CATFISH (Pangasius hypophthalmus) TOFU NUGGETS VACUUMAND NONVACUUM PACKED DURING COLDSTORAGE (50C) - Sahliana, Sahliana; Syahrul, Syahrul; Hasan, Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT This studyaims to compare the quality of catfish (Pangasius hypophthalmus) tofu nuggets vacuum and nonvacuumpackaged during cold storage (50C).  The treatments given consisted of (A1) vacuum packaging and (A2) nonvacuum packaging.  The quality parameters tested were organoleptic (appearance, aroma, taste and texture), Total Plate Count (TPC), and Total Volatile Base (TVB), with interval periods of 0, 4, 8, 12, and 16 days of storage.  The catfish tofu nuggets with vacuum packed are good quality with appearance characterisrics (dry bread crumbs, less bright, product specifications), taste (less strong, product specifications), aroma (less strong, product specifications), texture (rather solid and compact);  TVB 20.43 mgN / 100g;  TPC 4,7x104 colonies/g, with 12 days of cold storage.Keywords: Nugget,catfish, vacuum packaging, storage time